The use of fouling indexes in the pretreatment of saline waters prior to reverse osmosis desalination - Xing, Yongjie. (2008)
Current status of saline water processing and pretreatment processes prior to Reverse Osmosis (RO) desalination has been briefly reviewed. New trends and existing problems in this field have been found and presented.